Effects of different statin types and dosages on systolic/diastolic blood pressure: Retrospective analysis of 24‐hour ambulatory blood pressure database. Issue 5 (23rd April 2018) - Presta, Vivianne; Figliuzzi, Ilaria; Citoni, Barbara; Miceli, Francesca; Battistoni, Allegra; Musumeci, Maria Beatrice; Coluccia, Roberta; De Biase, Luciano; Ferrucci, Andrea; Volpe, Massimo; Tocci, Giuliano
Abstract : We previously demonstrated lower diastolic blood pressure (BP) levels under statin therapy in adult individuals who consecutively underwent 24‐hour ambulatory BP monitoring and compared their levels to untreated outpatients. Here we evaluated systolic/diastolic BP levels according to different statin types and dosages. 987 patients (47.5% female, age 66.0 ± 10.1 years, BMI 27.7 ± 4.6 kg/m 2, clinic BP 146.9 ± 19.4/86.1 ± 12.1 mm Hg, 24‐hour BP 129.2 ± 14.4/74.9 ± 9.2 mm Hg) were stratified into 4 groups: 291 (29.5%) on simvastatin 10‐80 mg/d, 341 (34.5%) on atorvastatin 10‐80 mg/d, 187 (18.9%) on rosuvastatin 5‐40 mg/d, and 168 (17.0%) on other statins. There were no significant BP differences among patients treated by various statin types and dosages, except in lower clinic ( P = .007) and daytime ( P = .013) diastolic BP in patients treated with simvastatin and atorvastatin compared to other statins. Favorable effects of statins on systolic/diastolic BP levels seem to be independent of types or dosages, thus suggesting a potential class effect of these drugs.